DEVELOPING ENGLISH READING MATERIALS IN REPORT TEXT FOR STUDENTS OF ELECTRICAL ENGINEERING PROGRAM AT SMK NEGERI 2 MEDAN - Nur Hafni Fatimah; Meisuri Meisuri; Safrida Lubis (Universitas Negeri Medan, 2018)
The objective of this study was to develop the appropriate English reading materials in report text for students of electrical engineering program at SMK Negeri 2 Medan. This study was conducted by using Research and Development (R&D) design. The data were gathered by distributing questionnaires to 35 students of electrical engineering program and administering interview to the teacher. The result of this study was a set of developed teaching reading materials as supplementary entitled “English for Electrical Engineering Students” which covers of three chapters on the topics of (1) things in electrical about hammer drill, (2) natural phenomena about lightning and aurora, (3) social phenomena about short circuit and electric shock. It is also accompanied by documents such as syllabus, lesson plans, reading materials, worksheets, and assessments. Key words:Research and Development (R&D), Reading Materials, Report Text, Vocational School, Electrical Engineering Program.